1989
DOI: 10.1104/pp.90.1.330
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metabolites in the Reversible Light Activation of Pyruvate, Orthophosphate Dikinase in Zea mays Mesophyll Cells in Vivo

Abstract: Whole leaf and mesophyll cell concentrations of pyruvate, phosphoenolpyruvate (PEP), ATP, and ADP were determined in Zea mays during the reversible light activation of pyruvate, orthophosphate dikinase in vivo. Mesophyll cell levels of the four metabolites were estimated by extrapolation from values in freeze-quenched leaf samples that were fractionated by differential filtration through nylon mesh nets (adapted from M Stitt, HW Heldt [1985] Planta 164: 179-188). During the 3 minutes required for complete lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
3

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“…These studies confirmed that PDRP is a Ser/Thr kinase that requires a phosphorylated His in the target enzyme (Burnell and Hatch, 1986). This regulatory threonyl phosphorylation of PPDK is a monocyclic cascade (Stadtman and Chock, 1977) in which the covalent modification system is assumed to be a continuous process that allows the extent of PPDK activation to be attuned to the metabolic needs (Roeske and Chollet, 1989). Therefore, PDRP can alter the activation state of its target enzyme, PPDK, according to the concentrations of metabolites (e.g.…”
supporting
confidence: 51%
“…These studies confirmed that PDRP is a Ser/Thr kinase that requires a phosphorylated His in the target enzyme (Burnell and Hatch, 1986). This regulatory threonyl phosphorylation of PPDK is a monocyclic cascade (Stadtman and Chock, 1977) in which the covalent modification system is assumed to be a continuous process that allows the extent of PPDK activation to be attuned to the metabolic needs (Roeske and Chollet, 1989). Therefore, PDRP can alter the activation state of its target enzyme, PPDK, according to the concentrations of metabolites (e.g.…”
supporting
confidence: 51%
“…1; Burnell and Hatch, 1985;Roeske and Chollet, 1989;Ashton et al, 1990). These same studies have not yielded a conclusive understanding of exactly how its opposing protein kinase and phosphatase activities are regulated, but a proposed mechanism involves the balance of competing substrates for RP (primarily ADP and Pi) in the chloroplast stroma (Burnell and Hatch, 1985;Roeske and Chollet, 1989;Ashton et al, 1990, Malkin andNiyogi, 2000). According to this working model, lower levels of stromal ADP in the light favor the reactivation/dephosphorylation (PP i -forming) reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although C 4 RP has not been reproducibly purified to homogeneity (compare Burnell and Hatch, 1985;Roeske and Chollet, 1987;Smith et al, 1994b) and therefore no related antibodies or gene clones presently exist, studies of the partially purified enzyme have elucidated a general reaction mechanism ( Fig. 1; Burnell and Hatch, 1985;Roeske and Chollet, 1989;Ashton et al, 1990). These same studies have not yielded a conclusive understanding of exactly how its opposing protein kinase and phosphatase activities are regulated, but a proposed mechanism involves the balance of competing substrates for RP (primarily ADP and Pi) in the chloroplast stroma (Burnell and Hatch, 1985;Roeske and Chollet, 1989;Ashton et al, 1990, Malkin andNiyogi, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations